2018
DOI: 10.1016/j.cotox.2017.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Environmental toxicant exposures and type 2 diabetes mellitus: Two interrelated public health problems on the rise

Abstract: Rates of type 2 diabetes mellitus (T2DM) are rising rapidly across the globe and the impact of this devastating disease threatens to plague the 21 century. While some contributing factors are well-recognized (e.g. sedentary lifestyles and caloric excess), others diabetes-promoting risk factors are less established or poorly appreciated. The latter category includes environmental exposures to diabetogenic contaminants. Herein we review some of the latest concepts and mechanisms by which environmental exposures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 79 publications
(86 reference statements)
1
26
0
Order By: Relevance
“…Humans are exposed to environmental chemicals on a daily basis, such as EDCs found in personal care products [ 56 ], plastics or food packaging [ 57 ] and the surrounding environment [ 58 ]. EDCs are known to disrupt the endocrine and metabolic homeostasis in the body, but other potential consequences include decreased reproductive function [ 57 , 59 , 60 ], neurodevelopmental delays in children [ 61 ] and increased risk of diabetes [ 62 ], or other chronic disorders via transgenerational inheritance of these exposures [ 63 ]. A worrisome observation is the fact that exposure to EDCs has increased >10-fold over the past ten years [ 64 ].…”
Section: Why Study Exposure To Environmental Toxins In Future Fathersmentioning
confidence: 99%
“…Humans are exposed to environmental chemicals on a daily basis, such as EDCs found in personal care products [ 56 ], plastics or food packaging [ 57 ] and the surrounding environment [ 58 ]. EDCs are known to disrupt the endocrine and metabolic homeostasis in the body, but other potential consequences include decreased reproductive function [ 57 , 59 , 60 ], neurodevelopmental delays in children [ 61 ] and increased risk of diabetes [ 62 ], or other chronic disorders via transgenerational inheritance of these exposures [ 63 ]. A worrisome observation is the fact that exposure to EDCs has increased >10-fold over the past ten years [ 64 ].…”
Section: Why Study Exposure To Environmental Toxins In Future Fathersmentioning
confidence: 99%
“…It is now clear that type 2 diabetes and non-alcoholic fatty liver disease can also be programmed in utero and early life by exposure to environmental chemicals in animal models. 40,42,43 An examination of environmental chemicals that caused obesity, type 2 diabetes or fatty liver diseases showed that exposure to many of the same chemicals led to all three diseases. Thus, it has been proposed that they should be called metabolism disrupting chemicals (MDCs or metabolism disruptors) as they can lead to metabolic syndrome.…”
Section: F I G U R E 2 Transgenerationalmentioning
confidence: 99%
“…While tremendous stress may be placed on β-cells from a metabolic standpoint, they also face other insults from environmental factors such as endocrine-disrupting chemicals (EDCs). EDCs may work alone or synergistically to derange the normal compensatory mechanisms enabling β-cells to promote glucose tolerance in insulin-resistant individuals (6). In this sense, EDCs may act as drivers of diabetes risk, becoming more deleterious as they compound with lifestyle factors and genetic susceptibilities.…”
Section: Introductionmentioning
confidence: 99%